Mood structures and their functions to reveal white's dominance: A critical discourse analysis in Doris Lessing's The Grass is Singing - Nursanti, Emi (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
This discourse study aims to analyze the structure and function of the modes in the speech of the characters in The Grass is Singing concerning white domination over black people. This is a qualitative study with a critical discourse analysis approach. The findings conform Fairclough's theory (1989) that the mood structure, whether declarative, interrogative, or imperative, can show the speaker's dominance and power. In the declarative mode, the speaker or the person giving the information tends to be in a higher position than the interlocutor. In the interrogative and imperative modes, the person who asks for both information and action from the interlocutor is generally more dominant. These findings reveal that white people consider their group to be superior to black people even though within the white group itself a social class division exists where those who are more successful will be more powerful than people who are struggling economically.